(untitled) (Applied Research and Innovation, 2023)
Ionizing radiation has hazardous effects on humans, from cell damage to complete organ failure, depending on the radiation energy and the exposure time. A well-designed diet could treat and reduce or delay radiation hazards. This study aimed to enhance immunity and monitor the effect of four designed diets on the 6 Gy irradiated rats. 1010 lacteal forte, two groups of rats were fed 5 and 10% garlic, and another two groups were fed 5 and 10% banana peels. Parameters related to nutrition and vitality were tracked. Comparing the effects of both kinds of treatment showed that the 5% garlic treatment had the best result on nutritional parameters, whereas the 10% garlic treatment had the best results from the side of medicine. Also, the 5 and 10% banana peel groups showed acceptable treatment results. Garlic as a food and banana peels as a food waste could be helpful in the presence of lacteal forte to treat and overcome the harmful hazard of radiation.